Development of a 3D tangible-serious game for attention improvement. (1st January 2014) - Roh, Chang Hyun; Lee, Wan Bok
There is a report that more than 10% of Korean elementary school students are classified into attention deficit/hyperactivity disorder (ADHD) symptom group. Children who seriously lack attention, like the ones with ADHD, are mainly dependent on medication. Medication, however, brings various kinds of side effects. Therefore, we need a way to improve attention, and lead children to voluntarily participate in it. In this study, we suggested a child-friendly attention improvement model by using children's favourite games. In addition, we developed a 3D tangible-serious game based on the suggested model. We conducted an experiment to identify the effects of the game developed in this study. As a result of the experiment, we could verify that the 3D tangible-serious game, which was developed in this study, helped improve children's attention.